The karyotype of Cabassous unicinctus (Dasypodidae, Xenarthra) - Pereira Junior, Helio Rubens Jacintho [UNESP]; Santiloni, Valquiria [UNESP]; Rosa, Patricia Sanmarco; Mota, Ligia Souza Lima Silveira da [UNESP]; Jorge, Wilham [UNESP] (Univ Florence Botany Inst, 2009)
Armadillos was belonged to the Xenarthra Order, Dasypodidae family This family has been comprising the largest number of genera and species among the Xenarthrans; eight (8) and 21, respectively. Two adult males of the species Cabassous unicinctus were analyzed in this study. Lymphocyte cultures from whole blood were used and the cells were then submitted to conventional staining by C- and Ag-NOR banding. Data regarding the number of chromosomes showed discrepancies among the species described in the literature. The 46 chromosomes observed were distributed in six large metacentric pairs, five medium submetacentric pairs, five medium and small metacentric pairs and six acrocentric pairs. The Y chromosome was classified such as the smallest acrocentric of the group. The X chromosome was classified as medium submetacentric, it considered atypical for mammals, because X was generally large size metacentric when it compared to the remaining karyotype. The diploid number reduction from 62 to 46 chromosomes may be explained by Robertsonian fusion and the inversion of acrocentric, or even the fission of centromeric regions of metacentric, given that the species Cabassous centralis had 23 acrocentric pairs and that this number was reduced to 14 pairs in the Cabassous tautouay and six pairs in the species described in the present work.
Keywords: Cabassous; chromosome evolution; Cingulata; Dasypodidae; karyotype; Xenarthra